Regenerative Medicine for Knee Osteoarthritis – The Efficacy and Safety of Intra-Articular Platelet-Rich Plasma and Mesenchymal Stem Cells Injections: A Literature Review - Ip, Hoi Leng (Cureus, 2020)
The prevalence of osteoarthritis (OA) has been rising exponentially in recent years. As the disease progresses, patients may eventually require surgical intervention to restore the functionality of the affected knees. The current literature review aims to explore two treatment options in regenerative medicine for OA by analyzing the efficacy and safety of platelet-rich plasma (PRP) and mesenchymal stem cells (MSCs) use, as well as determining which population will benefit from these treatments. A total of 1093 patients who were diagnosed with unilateral or bilateral knee osteoarthritis (KOA) were recruited in 23 studies. The experimental groups received either PRP or MSCs injections in comparison to the control groups receiving either hyaluronic acid (HA) or placebo (saline or dextrose) injections. Western Ontario and McMaster Universities Arthritis Index (WOMAC) was used to evaluate all participants at different time intervals of the studies. Medical imaging evaluations (X-ray or MRI) were used to look for structural improvements. In conclusion, both PRP and MSCs treatments were well tolerated, effective and safe to use. Repeated administrations and higher concentrations resulted in superior clinical improvements. A decrease in cartilage loss was observed in some MSCs trials. No severe adverse effects were documented. PRP treatment proved to be more efficacious among patients with KOA Kellgren-Lawrence (KL) grade I-II, while MSCs treatment proved to be more beneficial among the KOA KL grade II-III group.